Perception of parents about the social inclusion of newborns diagnosed with Down Syndrome: Experience report (Research, Society and Development, 2021)
Down Syndrome (DS) is a genetic alteration, therefore it is not hereditary, being considered the most common one that exists. The aim of this study was to report an experience about the perception of parents and / or guardians about the social inclusion of newborns diagnosed with Down syndrome. This is an experience report, carried out through an educational action, with a qualitative and descriptive approach, developed in an Association of Parents and Friends of the Exceptional (APAE), in the Metropolitan Region of Belém, in the state of Pará, carried out during the period in the afternoon of 10/22/2018. The educational action aimed to clarify the doubts and concerns of parents and / or legal guardians of people with DS, about the trisomy of chromosome 21 and demystify discrimination in the social sphere that the child may suffer, making it easier to include it. Despite the difficulties, it was possible to realize from the parents that the birth of a child with DS brings increased responsibilities, but their arrival is seen as a gift, and the affection they receive from the child is a way to compensate for the difficulties of daily life. The effective importance of nursing is perceived in this context, as we are opinion makers, and, in essence, educators. The health professional must share information about the health and care of the child with DS, so that their parents can make decisions necessary for their development.